Reliability of post natal gestational assessment: Capurro test compared with ultrasound at 10+0 to 14+2 weeks of gestation - Ventura Laveriano, Walter Ricardo (2015)
Objective: To compare gestational age assessed by Capurro test versus the gold standard, the first trimester ultrasound (10+0 to 14+2 weeks) in women with reliable last menstrual period. Design: Retrospective and correlation study. Setting: Instituto Nacional Materno Perinatal, Lima, Perú. Participants: Fetuses and the same once born. Methods: Ultrasound study was performed to 167 pregnant women at 10+0 to 14+2 weeks of gestation during the period 2005 through 2009; gestational age at birth of fetuses calculated by ultrasound was compared with gestational age by Capurro test. Main outcome measures: Comparison of medians of Wilcoxon test, interclass correlation coefficient, Lin’s coefficient concordance correlation, Bland & Altman’s graphic limits of agreement. Results: Mean gestational age assessed by Capurro test was 39 weeks versus 38 weeks determined by the crown rump length (Wilcoxon test z=-3.88, P<0.01). The intraclass correlation coefficient was 0.67 (95%CI: 0.58-0.75), the Lin’s coefficient concordance correlation was 0.65 (95%CI: 0.55-0.72), and the Bland & Altman limits of agreement was -0.41 (95%LOA -2.9-2.1). Conclusions: Gestational age assessment by Capurro test tended to overestimate age. The relation between these two methods was not perfect as measurements were different.